Familia y asertividad en adolescentes que asisten a Centros Comunales - Benites Morales, Luis (2006)
The relation between the type of family, family social environment and the assertiveness was investigated in 117 adolescents, 51 men and 66 women of 12 Community Center for the life the peace of INABIF (Lima). The method was comparative and correlational. The instruments were Family Environment Scale (FES) of Moos and Moos, Assertiveness scale of García y Magaz (ADCA.1) and a family survey. Nuclear, extended, and blended families and other family types present a Bad category of familysocial environment in the Relation and Development dimensions. In the Stability dimension almost all have an Ambivalent category. The adolescent’s self-assertiveness and hetero assertiveness is Average in the extend family and Lowe in the rest of families. Development and subscales: Autonomy and Intellectual – Cultural FES. There are no differences among family levels of self-assertiveness and hetero assertiveness, being significant the correlation families levels of self- assertiveness in extended families and non-classified families. High values in Expression and autonomy promoted development of assertiveness.